Penerapan Model Pembelajaran Quantum Teaching untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa Kelas IV SD - Dyah Wahyuning Astrini; Khusnul Khotimah; Puri Selfi Cholifah (Universitas Negeri Malang, 2021)
Abstract: This research aims to describe implementation of the Quantum Teaching learning model to increase student activity and learning outcomes of 4th grade students at Sentul II State Elementary School Purwodadi Pasuruan. The research subjects are 4th grade students at Sentul II State Elementary School. This research uses classroom action research conducted in two cycles. The results of the research showed an increase in student activity which was seen from visual activities, oral activities, writing activities, emotional activities, motor activities, and mental activities. The learning outcomes of 4th grade students which was seen from students' classical learning completeness in the first cycle is 55 percent increasing to 80 percent in the second cycle. The average grade increased from 61 to 73. So, it can be concluded that the application of the Quantum Teaching learning model can increase student activity and learning outcomes of 4th grade students at Sentul II State Elementary School Purwodadi Pasuruan. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan model pembelajaran Quantum Teaching untuk meningkatkan keaktifan siswa dan hasil belajar siswa kelas IV SD Negeri Sentul II Purwodadi Pasuruan. Subjek penelitian yang digunakan adalah siswa kelas IV SDN Sentul II yang berjumlah 20 orang. Penelitian ini menggunakan penelitian tindakan kelas yang dilakukan dalam dua siklus dengan rincian setiap siklus terdiri dari dua pertemuan. Hasil penelitian menunjukkan adanya peningkatan keaktifan siswa dari siklus I ke siklus II yang dilihat dari visual activities, oral activities, writing activities, emotional activities, motoric activities, dan mental activities. Hasil belajar siswa kelas IV juga mengalami peningkatan dilihat dari ketuntasan belajar klasikal siswa pada siklus I sebesar 55 persen meningkat menjadi 80 persen pada siklus II. Rata-rata nilai di kelas tersebut juga mengalami peningkatan dari 61 menjadi 73. Sehingga, dapat disimpulkan bahwa penerapan model pembelajaran Quantum Teaching dapat meningkatkan keaktifan siswa dan hasil belajar siswa kela 4 SDN Sentul II Purwodadi Pasuruan.